Linguistics and Psychoanalysis : Freud, Saussure, Hjelmslev, Lacan and Others. - Arrivé, Michel (Semiotic crossroads ;, 1992)
If you read or reread Freud, it is difficult not to find on a single page references to language: from speech to text, from slip of the tongue to word play, from letter to meaning-passing inevitably through the strange notion of literal meaning, that fascinated Freud. In short, the unconscious is linked to language. How could it be otherwise, if psychoanalysis is a cure through speech as indicated as early as 1881, by Fraülein Anna O.? The problem of the relationship between linguistic and psychoanalytic concepts necessarily arises. Until now this question has been examined mainly by psychoana.